2021
DOI: 10.1002/er.7169
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electrochemical properties of Al‐F co‐doped spinel LiMn 2 O 4 single‐crystal material for lithium‐ion battery

Abstract: Summary Spinel LiMn2O4 has the advantages of high voltage, high safety, low pollution, low cost, and rich resources. However, its low initial capacity, rapid‐cycle decay, and other factors hinder its commercialization process. In this paper, a pure phase LiMn2O4 is synthesized by a high‐temperature solid‐phase method, and the element doping is used to modify it to improve its cycle performance. The results show that the optimal process conditions for preparing LiMn2O4 are: the Li/Mn ratio is 1.05:2, the calcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Co-doping of two or more elements.-In addition to singleelement doping, the co-doping of two or more elements has been explored as a way of enhancing the overall electrochemical performance and cycling stability of LMO. Li et al 134 synthesized LMO through a high-temperature solid-phase method and modified it with Al and F elements, resulting in the formation of a single crystal Li 1.05 Al 0.02 Mn 1.98 F 0.02 O 3.98 with uniform particle distribution and regular morphology. The electrochemical tests indicated that the sample had excellent cycling performance, with an initial discharge capacity of 115.5 mAh g −1 at 0.1 C. After 367 cycles, the discharge specific capacity was 90.3 mAh g −1 , and the capacity retention rate was over 80%.…”
Section: Modification Of Limn 2 O 4 Cathode Materialsmentioning
confidence: 99%
“…Co-doping of two or more elements.-In addition to singleelement doping, the co-doping of two or more elements has been explored as a way of enhancing the overall electrochemical performance and cycling stability of LMO. Li et al 134 synthesized LMO through a high-temperature solid-phase method and modified it with Al and F elements, resulting in the formation of a single crystal Li 1.05 Al 0.02 Mn 1.98 F 0.02 O 3.98 with uniform particle distribution and regular morphology. The electrochemical tests indicated that the sample had excellent cycling performance, with an initial discharge capacity of 115.5 mAh g −1 at 0.1 C. After 367 cycles, the discharge specific capacity was 90.3 mAh g −1 , and the capacity retention rate was over 80%.…”
Section: Modification Of Limn 2 O 4 Cathode Materialsmentioning
confidence: 99%
“…Compared to single-element doping strategies, element codoping strategies have recently attracted wide attention due to the different roles of different doping ions in the structure. 25,27,28 The synergistic effects integrate and amplify the influences of different doping ions, providing new avenues for the design and development of high-performance LiMn 2 O 4 cathode materials. Therefore, if a simple and inexpensive synthesis method could be proposed to simultaneously incorporate Li + and PO 3− codoping effectively inhibits the irreversible phase transition of spinel LiMn 2 O 4 from cubic phase to tetragonal phase, improving the cycling stability of electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, large-size PO 4 3– doping would lead to local structural distortions and stress concentration in the spinel structure. , Therefore, such doping strategies need to be combined with other means to achieve better modification effects. Compared to single-element doping strategies, element codoping strategies have recently attracted wide attention due to the different roles of different doping ions in the structure. ,, The synergistic effects integrate and amplify the influences of different doping ions, providing new avenues for the design and development of high-performance LiMn 2 O 4 cathode materials. Therefore, if a simple and inexpensive synthesis method could be proposed to simultaneously incorporate Li + and PO 4 3– into spinel LiMn 2 O 4 , it is likely to achieve the synergistic effects of element codoping and realize overall improvement in cycling performance and rate capability of spinel LiMn 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly associated with the structural instability that originates from the Jahn-Teller effect, Mn solvation, oxygen defects, and so on. [9][10][11][12][13] Up to now, several strategies for stabilizing the crystal structure of the spinel LiMn 2 O 4 cathode materials have been reported, such as element doping, surface coating, particle morphology control, and process optimization. [14][15][16][17] Among them, element doping is acknowledged as a more satisfactory strategy to mitigate the Jahn-Teller effect.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly associated with the structural instability that originates from the Jahn–Teller effect, Mn solvation, oxygen defects, and so on. 9–13…”
Section: Introductionmentioning
confidence: 99%